Investigation of Failure Criteria and Experimental Process of the Composite Specimen with Mechanical Joints under Tensile Loading - Fathi, Pourya; Moslemi Petrudi, Amin (Journal of Modern Materials, 2020)
Generally, composite materials are used to obtain better engineering properties, including higher hardness, greater strength, lower weight, heat resistance, moisture and corrosion, which are not present in homogeneous materials such as metals, which are more commonly used in composite design. In this article, experimental study of the composite specimen with mechanical joints under tensile loading, joints of composite material structures, failure criteria in composite materials, tensile impact test is investigated. The results of research work it shows that maximum strength, the hand lay-up can be designed with [0º, 45º, 90º, -45º] s and layers with 45º fibers is very important, because these fibers in these layers have a significant role in increasing the resistance of the piecework under shear stresses due to the passage of stress lines along the hole; In other words, the maximum cut occurs at a 45º angle, and these layers resist this shear stress.